IN VITRO ANTIPLASMODIAL ACTIVITY OF NATIVE INDIAN SEAWEED SARGASSUM SP. - R, SOWMIYA; S, Prasanna Kumar; P, Deepak; R, Ramkumar; G, Balasubramani; D, Aiswarya; P, Perumal; S, RAVIKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: To investigate the antiplasmodial activity of three different solvent extracts of Sargassum tenerrimum against Plasmodium falciparum. Methods: The seaweed species of S. tenerrimum were collected from Rameshwaram, Southeast coast of India. The collected samples were dried and extracted with three different polaritic (hexane, acetone, and ethylacetate) solvents and tested against P. falciparum parasite strain. Results: Acetone extract exhibited better activity than the other two extracts. The inhibitory concentration values of acetone S. tenerrimum were found to be 27.82 and 18.14 Âµg/ml at 24-48 hrs, respectively. S. tenerrimum crude extracts were subjected for the phytochemical analysis, and it showed the presence of steroids, alkaloids, flavonoids, tannins, glycosides, amino acids, and phenol compounds. The gas chromatography-mass spectroscopy result reveals that the presence of 10 major and minor compounds in the S. tenerrimum extract. In that, cyclotrisiloxane hexamethyl compounds might be responsible for the effective parasite suppression. 50 Conclusion: It can be concluded from the present study that the acetone extract of S. tenerrimum has strong antiplasmodial activity. Furthermore, the study has been extended to the isolation of the possible active compounds that is responsible for the antiplasmodial properties. Keywords: Antiplasmodial assay, Different polaritic solvents, Plasmodium falciparum, Sargassum tenerrimum.